The "Spatial Practice" in a Mountainous Village in Modern Japanese Society: Various Strata of "Lived- Space," as Seen at Ouchi, Minami Aizu - MASUGATA, Toshiko (Japanese Sociological Review, 2010)
Ouchi district of Simogou Town in Fukushima Prefecture prospered during the early Edo Era as a rest stop on the main Aizu West Road, but it was left behind in the transport revolution of the Meiji Era because of its remote mountainous location. As a result, a "lived-space" containing an abundant "rotating time" was created in it. After the post-war reconstruction and into the latter half of the 1960s, however, the people of Ouchi were rather disrupted by frequent waves of modernization such as dam development, legislative selection to the "Preservation Districts for Groups of Traditional Buildings," tourism, and resort development. This paper studies the case of Ouchi by focusing on preserving the rest stop and developing tourism and by studying their spatial practices to determine in what different dimension they have introduced the modernization and how the contradictory order and system was formed within it. In order to approach this subject, the author has traced the spatial practices in modern Ouchi. The "representation of space" -the touristic space in Ouchi-was built through the practices that prioritize to maintaining the local life system. In consequence, the "lived-space" was variously created in the "representation of space" -Ouchi-where "rotating time" flows. In this "spatial practice" at Ouchi, we would find a perception that connects the "lived-space" and "rotating time" to the alternative production process of social organization and structure.